Adherence and persistence of mirabegron and anticholinergic therapies in patients with overactive bladder: a real‐world claims data analysis. Issue 3 (March 2017) - Sussman, D.; Yehoshua, A.; Kowalski, J.; Lee, W.; Kish, J.; Chaudhari, S.; Murray, B.
Summary: Background: Adherence and persistence rates of anticholinergic (ACH) therapies have been well described. To date, few studies describe these metrics for mirabegron in patients with overactive bladder. Methods: This retrospective analysis of MarketScan ® database assessed adherence and persistence of patients receiving either mirabegron or ACH. Study eligibility required an index date (first prescription filled) between July 2012 and June 2013 with 12 months of continuous enrolment preindex date and 12 months of follow‐up. Adherence was defined as a proportion of days covered of ≥ 80% among patients with at least 2 fills of index medication. Persistence measures included treatment failure described as either treatment discontinuation (medication supply gap ≥ 30 days) or switching to a different medication. A medication supply gap of ≥ 45 days was used as a sensitivity analysis. Results: The mean age of mirabegron users ( n = 4037) was 67 years and 43% were ACH naïve while the mean age of ACH users was 62 years ( n = 67, 943). Over the 12‐month follow‐up period, 44% of patients treated with mirabegron and 31% of patients treated with ACH were adherent to their indexed medications. Treatment failure was 81% for mirabegron and 88% for ACH. Most mirabegron treatment failures were because of treatment discontinuation (67%) versus switching to ACH therapy (14%). The ACH discontinuation rate was 84% and treatment switching rate was 4%. The mean (standard deviation) time to treatment failure was 143 (130) days for mirabegron and 69 (69) days for ACH. Adherence and persistence patterns were similar in the sensitivity analysis using a ≥ 45‐day supply gap threshold. Conclusions: This real‐world study demonstrated low adherence and persistence to mirabegron similar to ACH therapies.